Negative electrode material for lithium ion secondary battery, negative electrode for lithium ion secondary battery, and lithium ion secondary battery

By using carbon materials with specific structure and particle size distribution in lithium-ion secondary batteries, the problem of difficulty in taking into account high energy density and high life characteristics in the prior art is solved, and efficient charging and discharge and long life battery performance are achieved.

CN114883558BActive Publication Date: 2025-03-18RESONAC CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202210750544.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2016-11-14
Publication Date
2025-03-18
Estimated Expiration
2036-11-14

AI Technical Summary

Technical Problem

It is difficult for existing lithium-ion secondary battery negative electrode materials to take into account high energy density and high life, especially at high temperatures, which have a high reactivity with the electrolyte, which affects the battery life.

Method used

The carbon material determined by X-ray diffraction method is used, with an average surface spacing d002 between 0.335 nm and 0.339 nm, and a specific surface area determined by nitrogen adsorption is between 0.5 m2/g and 6.0 m2/g. The composite material is formed through specific particle size distribution and combination to improve battery performance.

Benefits of technology

It achieves the improvement of the input and output characteristics and life characteristics of lithium-ion secondary batteries while maintaining high charge and discharge efficiency, and is suitable for high capacity requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003718110610000071
    Figure BDA0003718110610000071
  • Figure BDA0003718110610000251
    Figure BDA0003718110610000251
Patent Text Reader

Abstract

The present invention provides a negative electrode material for a lithium ion secondary battery, a negative electrode for a lithium ion secondary battery, and a lithium ion secondary battery. The negative electrode material for a lithium ion secondary battery comprises a carbon material, wherein the average plane spacing d 002 The specific surface area is 0.335 nm to 0.339 nm, and the specific surface area is 0.5 m 2 / g~6.0m 2 / g, and the following (1) and (2) are satisfied. (1) In the number-based particle size distribution, the particle size at which the differential relative particle amount q0 becomes the most frequent value is less than or equal to 11.601 μm. (2) In the number-based particle size distribution, the ratio of the differential relative particle amount q0A when the particle size is 11.601 μm to the differential relative particle amount q0B when the particle size is 7.806 μm (q0A / q0B) is 1.20 to 3.00.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present invention is a divisional application of the invention application with application number 201680090827.3, application date November 14, 2016, and invention name “Negative electrode material for lithium-ion secondary battery, negative electrode for lithium-ion secondary battery, and lithium-ion secondary battery”. Technical Field

[0002] The present invention relates to a negative electrode material for a lithium ion secondary battery, a negative electrode for a lithium ion secondary battery, and a lithium ion secondary battery. Background Art

[0003] Lithium-ion secondary batteries are lighter and have higher input-output characteristics than other secondary batteries such as nickel-metal hydride batteries and lead-acid batteries. Therefore, they have recently attracted attention as high-input-output power sources used in electric vehicles and hybrid electric vehicles.

[0004] Since the commercialization of lithium-ion secondary batteries in 1991, there has been a strong desire to further improve their energy density and input-output characteristics. As a method for achieving this expectation, the technology of improving the negative electrode material contained in the negative electrode of lithium-ion secondary batteries occupies an important position (for example, see Patent Documents 1 and 2).

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Laid-Open No. 4-370662

[0008] Patent Document 2: Japanese Patent Application Laid-Open No. 5-307956 Summary of the Invention

[0009] Problems to be solved by the invention

[0010] As materials for negative electrode materials of lithium-ion secondary batteries, carbon materials such as graphite and amorphous carbon are widely used.

[0011] Graphite has a structure in which hexagonal networks of carbon atoms are regularly stacked. Charge and discharge are performed by the insertion and extraction reactions of lithium ions from the ends of the stacked networks.

[0012] Furthermore, because amorphous carbon has irregular hexagonal lattice stacking or no mesh structure, lithium ion insertion and extraction reactions occur across the entire surface, making it easy to obtain lithium ions with excellent input and output characteristics. Furthermore, in contrast to graphite, amorphous carbon has low crystallinity, which can suppress reactions with electrolytes and provide excellent lifespan characteristics.

[0013] Graphite, because lithium ion insertion and extraction reactions occur only at the ends, cannot be said to have sufficient input and output performance. Furthermore, due to its high crystallinity and high surface reactivity, its reactivity with the electrolyte sometimes increases, especially at high temperatures, leaving room for improvement in the lifespan characteristics of lithium-ion secondary batteries. On the other hand, amorphous carbon, because its crystallinity is lower than that of graphite, has an irregular crystal structure and cannot be said to have sufficient energy density.

[0014] Based on the above-mentioned differences in properties between graphite and amorphous carbon, a carbon material in a state where a layer of amorphous carbon is formed on the surface of a core material formed of graphite is proposed as a carbon material that can take into account both the high energy density derived from graphite and the high life characteristics derived from amorphous carbon.

[0015] In recent years, the demand for higher-capacity batteries has increased, particularly in automotive applications, to extend driving range. Consequently, as with consumer applications, research is underway to increase the density of electrodes in automotive applications. However, there are concerns about a decrease in input-output characteristics due to increased electrode density, and balancing high capacity with input-output characteristics has become a challenge. This requires addressing issues that are difficult to resolve simply by combining graphite with amorphous carbon.

[0016] An object of the present invention is to provide a negative electrode material for a lithium ion secondary battery and a negative electrode for a lithium ion secondary battery capable of producing a lithium ion secondary battery having excellent input-output characteristics and life characteristics while maintaining high charge and discharge efficiency, and a lithium ion secondary battery produced using the same.

[0017] Solutions to Problems

[0018] Means for solving the above-mentioned problems include the following embodiments.

[0019] <1> A negative electrode material for a lithium ion secondary battery, comprising a carbon material, wherein the average interplanar spacing d of the carbon material obtained by X-ray diffraction is 002 The specific surface area is 0.335 nm to 0.339 nm, and the specific surface area determined by nitrogen adsorption at 77 K is 0.5 m 2 / g~6.0m 2 / g, and satisfy the following (1) and (2).

[0020] (1) In the number-based particle size distribution, the particle diameter at which the differential relative particle amount q0 becomes the mode is 11.601 μm or less.

[0021] (2) In the number-based particle size distribution, the ratio (q0A / q0B) of the relative amount of differential particles q0A at a particle diameter of 11.601 μm to the relative amount of differential particles q0B at a particle diameter of 7.806 μm is 1.20 to 3.00.

[0022] <2> A negative electrode material for a lithium ion secondary battery, comprising a carbon material, wherein the average interplanar spacing d of the carbon material determined by X-ray diffraction is 002 The wavelength is 0.335 nm to 0.339 nm, the R value determined by Raman spectroscopy is 0.1 to 1.0, and the following (1) and (2) are satisfied.

[0023] (1) In the number-based particle size distribution, the particle diameter at which the differential relative particle amount q0 becomes the mode is 11.601 μm or less.

[0024] (2) In the number-based particle size distribution, the ratio (q0A / q0B) of the relative amount of differential particles q0A at a particle diameter of 11.601 μm to the relative amount of differential particles q0B at a particle diameter of 7.806 μm is 1.20 to 3.00.

[0025] <3> A negative electrode material for a lithium ion secondary battery, comprising a carbon material, wherein the average interplanar spacing d of the carbon material obtained by X-ray diffraction is 002 It is 0.335 nm to 0.339 nm, includes a first carbon phase serving as a core, and a second carbon phase different from the first carbon phase and arranged on at least a portion of the surface of the first carbon phase, and satisfies the following (1) and (2).

[0026] (1) In the number-based particle size distribution, the particle diameter at which the differential relative particle amount q0 becomes the mode is 11.601 μm or less.

[0027] (2) In the number-based particle size distribution, the ratio (q0A / q0B) of the relative amount of differential particles q0A at a particle diameter of 11.601 μm to the relative amount of differential particles q0B at a particle diameter of 7.806 μm is 1.20 to 3.00.

[0028] <4> According to any one of <1> to <3>, in the volume-based particle size distribution of the above-mentioned carbon material, when the volume cumulative distribution curve is drawn from the smaller particle size side, the cumulative value Q3 when the particle size is 9.516 μm is greater than or equal to 4.0% of the total.

[0029] <5> According to any one of <1> to <4>, in the volume-based particle size distribution of the above-mentioned carbon material, when the volume cumulative distribution curve is drawn from the smaller particle size side, the particle size (50%D) when the accumulation becomes 50% is 1μm to 20μm.

[0030] <6> According to any one of <1> to <5>, in the volume-based particle size distribution of the above-mentioned carbon material, when the volume cumulative distribution curve is drawn from the small particle size side, the particle size (99.9%D) when the accumulation becomes 99.9% is less than or equal to 63μm.

[0031] <7> The negative electrode material for a lithium ion secondary battery according to any one of <1> to <6>, wherein the tap density of the carbon material is 0.90 g / cm 3 ~2.00g / cm 3 .

[0032] <8> The negative electrode material for a lithium ion secondary battery according to any one of <1> to <7>, wherein the particle density of the carbon material is less than or equal to 1.55 g / cm 3 .

[0033] <9> A negative electrode for a lithium ion secondary battery, comprising a negative electrode material layer and a current collector, wherein the negative electrode material layer comprises the negative electrode material for a lithium ion secondary battery according to any one of <1> to <8>.

[0034] <10> A lithium ion secondary battery comprising the negative electrode for a lithium ion secondary battery according to <9>, a positive electrode, and an electrolyte.

[0035] Effects of the Invention

[0036] The present invention provides a negative electrode material for a lithium ion secondary battery, a negative electrode for a lithium ion secondary battery, and a lithium ion secondary battery produced using the negative electrode material, which can produce a lithium ion secondary battery having excellent input / output characteristics and life characteristics while maintaining high charge and discharge efficiency. DETAILED DESCRIPTION

[0037] Hereinafter, the mode for implementing the present invention will be described in detail. However, the present invention is not limited to the following embodiments. In the following embodiments, the constituent elements (including element steps, etc.) are not necessarily required except for the cases specifically indicated. The same is true for numerical values ​​and their ranges, and the present invention is not limited thereto.

[0038] In this specification, the term "process" includes processes that are independent of other processes and processes that cannot be clearly distinguished from other processes as long as the purpose of the process can be achieved.

[0039] In this specification, a numerical range expressed using “to” includes the numerical values ​​described before and after “to” as the minimum value and the maximum value, respectively.

[0040] In the numerical ranges described in this specification, the upper limit or lower limit of one numerical range may be replaced by the upper limit or lower limit of another numerical range described in this specification. In addition, in the numerical ranges described in this specification, the upper limit or lower limit of the numerical range may be replaced by the value shown in the examples.

[0041] In this specification, when a plurality of substances corresponding to components are present in a composition, the content rate or content of each component in the composition refers to the total content rate or content of the plurality of substances present in the composition unless otherwise specified.

[0042] In this specification, when a plurality of particles corresponding to each component are present in a composition, the particle size of each component in the composition refers to a value for a mixture of the plurality of particles present in the composition unless otherwise specified.

[0043] In this specification, the term "layer" or "film" includes not only a case where the layer or film is formed in the entire region but also a case where the layer or film is formed in only a part of the region when observing a region where the layer or film exists.

[0044] In this specification, the term "stacked" means stacking layers, and two or more layers may be combined or detachable.

[0045] <Negative electrode materials for lithium-ion secondary batteries (1)>

[0046] The negative electrode material for lithium ion secondary battery of this embodiment (hereinafter sometimes simply referred to as “negative electrode material”) includes a carbon material, and the average interplanar spacing d of the carbon material determined by X-ray diffraction is 002 The specific surface area is 0.335 nm to 0.339 nm, and the specific surface area determined by nitrogen adsorption at 77 K is 0.5 m 2 / g~6.0m 2 / g, and satisfy the following (1) and (2).

[0047] (1) In the number-based particle size distribution, the particle diameter at which the differential relative particle amount q0 becomes the mode is 11.601 μm or less.

[0048] (2) In the number-based particle size distribution, the ratio (q0A / q0B) of the relative amount of differential particles q0A at a particle diameter of 11.601 μm to the relative amount of differential particles q0B at a particle diameter of 7.806 μm is 1.20 to 3.00.

[0049] By using the negative electrode material of this embodiment, a lithium ion secondary battery can be manufactured that is excellent in input-output characteristics and life characteristics while maintaining high charge and discharge efficiency.

[0050] The composition of the negative electrode material of the present embodiment is not particularly limited as long as it contains a carbon material that meets the above conditions. From the perspective of obtaining the effect of the present embodiment, the proportion of the carbon material in the negative electrode material as a whole is preferably greater than or equal to 50% by mass, more preferably greater than or equal to 80% by mass, further preferably greater than or equal to 90% by mass, and particularly preferably 100% by mass.

[0051] (Carbon material)

[0052] The average interplanar spacing d of the carbon material obtained by X-ray diffraction 002 It is 0.335nm~0.339nm.

[0053] Average surface spacing d 002 The value of 0.3354 nm is the theoretical value of graphite crystal, and there is a tendency that the closer to this value, the higher the energy density becomes. 002 When the value of is within the above range, there is a tendency for excellent initial charge and discharge efficiency and energy density of the lithium ion secondary battery to be obtained.

[0054] In this embodiment, the average interplanar spacing d of the carbon material 002 The carbon material sample can be irradiated with X-rays (CuKα rays), the diffraction spectrum obtained by measuring the diffraction lines using a goniometer, and the Bragg formula can be used to calculate the diffraction peak corresponding to the carbon 002 plane that appears near the diffraction angle 2θ = 24° to 27°.

[0055] From the perspective of energy density of lithium-ion secondary batteries, the average interplanar spacing d of the carbon material is 002 The value of is preferably small. Specifically, for example, it is preferably 0.335 nm to 0.337 nm.

[0056] Average interplanar spacing d of carbon materials 002 The value of d tends to decrease, for example, by increasing the temperature of the heat treatment of the carbon material. Therefore, this property can be used to reduce the average interplanar spacing d. 002 Adjust to within the above range.

[0057] The specific surface area of ​​the carbon material obtained by nitrogen adsorption measurement at 77K (hereinafter sometimes referred to as N2 specific surface area) is 0.5 m 2 / g~6.0m 2 / g.

[0058] When the N2 specific surface area of ​​the carbon material is within the above range, there is a tendency for the balance between the input-output characteristics and the primary efficiency to be well maintained.

[0059] The N2 specific surface area of ​​the carbon material can be determined by the BET method based on the adsorption isotherm obtained by nitrogen adsorption measurement at 77K.

[0060] From the perspective of the balance between the input-output characteristics and the initial efficiency of the lithium-ion secondary battery, the N2 specific surface area is preferably 1.0 m 2 / g~5.0m 2 / g.

[0061] The N2 specific surface area tends to be reduced by, for example, increasing the volume average particle size of the carbon material, increasing the temperature of the heat treatment of the carbon material, modifying the surface of the carbon material, etc. Therefore, this property can be used to set the N2 specific surface area within the above range.

[0062] In the number-based particle size distribution of the carbon material, the particle size at which the differential relative particle amount q0 becomes the mode is less than or equal to 11.601 μm. If the particle size at which the differential relative particle amount q0 becomes the mode exceeds 11.601 μm, the proportion of carbon material with a large particle size increases, thereby increasing the diffusion distance of lithium ions from the particle surface to the interior of the carbon material, and tending to reduce the input-output characteristics of the lithium-ion secondary battery.

[0063] The particle diameter when the differential relative particle amount q0 becomes the mode is preferably 11.601 μm or 9.516 μm, more preferably 11.601 μm.

[0064] In the carbon material, the total value of the difference in relative particle amount q0 when the particle size is 11.601 μm and the difference in relative particle amount q0 when the particle size is 9.516 μm is preferably greater than or equal to 25, more preferably greater than or equal to 30, and further preferably greater than or equal to 32.

[0065] In the number-based particle size distribution of the carbon material, the ratio of the relative particle amount q0A of the difference when the particle diameter is 11.601 μm to the relative particle amount q0B of the difference when the particle diameter is 7.806 μm (q0A / q0B) is 1.20 to 3.00.

[0066] If the value of q0A / q0B is less than 1.20, the input-output characteristics tend to deteriorate.

[0067] If the value of q0A / q0B exceeds 3.00, the contact between the carbon material particles deteriorates, and the life characteristics of the lithium ion secondary battery tend to decrease.

[0068] From the viewpoint of input-output characteristics and life characteristics, the value of q0A / q0B is preferably in the range of 1.20 to 2.20, and more preferably in the range of 1.25 to 2.10.

[0069] In this specification, the number-based particle size distribution of the carbon material can be obtained by dividing the particle size range of 0.1 μm to 2000 μm into 50 particles at a logarithmic ratio. For example, n = (2000 / 0.1)^(1 / 50) can be calculated and the particle size can be obtained based on 0.1×n, 0.1×n^2, ..., 0.1×n^50. The total value of the relative particle amount q0 for each particle size in the range of 0.1 μm to 2000 μm is 100.

[0070] Table 1 shows the value of the relative particle amount q0 of the difference based on the number of carbon materials used in Example 2 and the particle size.

[0071] [Table 1]

[0072]

[0073] In the volume-based particle size distribution of the carbon material, when a volume cumulative distribution curve is drawn from the smaller particle size side, the cumulative value Q3 at a particle size of 9.516 μm is preferably greater than or equal to 4.0% of the total, more preferably greater than or equal to 9.0%.

[0074] When the cumulative value Q3 at a particle size of 9.516 μm is equal to or greater than 4.0% of the total, the fine particles contained in the carbon material can sufficiently ensure contact points between particles, and the life characteristics of the lithium ion secondary battery tend to be improved.

[0075] The upper limit of the cumulative value Q3 is not particularly limited, but is preferably 30% or less, and more preferably 20% or less.

[0076] In the volume-based particle size distribution of the carbon material, when the volume cumulative distribution curve is drawn from the smaller particle size side, the particle size when the accumulation reaches 50% (50%D, hereinafter also referred to as the volume average particle size) is preferably 1 μm to 20 μm, more preferably 3 μm to 18 μm, and further preferably 5 μm to 15 μm.

[0077] If the volume average particle size of the carbon material is greater than or equal to 1 μm, there is a tendency to suppress the initial charge and discharge efficiency of the lithium ion secondary battery due to excessively large specific surface area. On the other hand, if the volume average particle size of the carbon material is less than or equal to 20 μm, it can suppress the tendency to suppress the input and output characteristics of the lithium ion secondary battery due to excessively large particle size, which leads to a longer diffusion distance of Li from the particle surface to the interior.

[0078] In the volume-based particle size distribution of the carbon material, when the volume cumulative distribution curve is drawn from the small particle size side, the particle size when the accumulation becomes 99.9% (99.9%D, hereinafter also referred to as the maximum particle size) is preferably less than or equal to 63 μm, more preferably less than or equal to 50 μm, and further preferably less than or equal to 45 μm.

[0079] When the maximum particle size of the carbon material is 63 μm or less, it is easy to reduce the thickness of the electrode plate when producing the electrode, and there is a tendency that the influence on the input-output characteristics can be suppressed.

[0080] In this specification, similar to the number-based particle size distribution, the volume-based particle size distribution of the carbon material can be obtained by logarithmically dividing the range of 0.1 μm to 2000 μm into 50. The volume-based particle size distribution can be measured by the same method as the number-based particle size distribution.

[0081] In this specification, the particle size distribution of the carbon material can be measured using a known method. For example, a dispersion prepared by dispersing a sample of the carbon material in purified water together with a surfactant is placed in a sample water tank of a laser diffraction particle size distribution measuring device, and ultrasonic waves are applied for 1 minute while circulating the sample in a pump, and the sample is measured by laser diffraction under the following measurement conditions. As a laser diffraction particle size distribution measuring device, for example, the "SALD-3000J" of Shimadzu Corporation can be used. Here, a number-based particle size distribution or a volume-based particle size distribution can be obtained by selecting "number" or "volume" as the output condition.

[0082] (Setting of measurement conditions)

[0083] Number of measurements: 1

[0084] Measurement interval: 2 seconds

[0085] Average number of times: 64 times

[0086] Absorbance range: 0.01~0.2

[0087] (Any particle size % table setting)

[0088] Range: 0.1μm~2000μm

[0089] Number of divisions: 50

[0090] The carbon material of the present embodiment can be obtained, for example, by combining two or more carbon materials having different particle sizes.

[0091] Examples of such combinations of carbon materials include a combination of a carbon material having a volume average particle size of 8 to 12 μm and a carbon material having a volume average particle size of 14 to 18 μm, a combination of a carbon material having a volume average particle size of 9 to 11 μm and a carbon material having a volume average particle size of 15 to 17 μm, and the like.

[0092] Examples of the ratio when combining two carbon materials having different particle sizes include a mass ratio in the range of 7:3 to 3:7 and a mass ratio in the range of 6:4 to 4:6.

[0093] The tap density of the carbon material is preferably 0.90 g / cm 3 ~2.00g / cm 3 , more preferably 1.00 g / cm 3 ~1.50g / cm 3 , more preferably 1.05 g / cm 3 ~1.30g / cm 3 .

[0094] If the tap density of the carbon material is greater than or equal to 0.90 g / cm 3 , the amount of organic matter such as the binder used in making the negative electrode can be reduced, and there is a tendency for the energy density of the lithium ion secondary battery to increase. On the other hand, if the tap density of the carbon material is less than or equal to 2.00 g / cm 3 , there is a tendency for the input-output characteristics to become better.

[0095] The tap density of the carbon material tends to increase, for example, by increasing the volume average particle size of the carbon material. This property can be utilized to set the tap density within the above range.

[0096] The tap density of the entire negative electrode material including the carbon material may be 0.90 g / cm 3 ~3.00g / cm 3 As a method for adjusting the tap density of the negative electrode material, there is a method of adding a metal component described later to the negative electrode material in addition to the carbon material.

[0097] In this specification, the tap density of a carbon material or a negative electrode material refers to the value obtained as follows (g / cm 3 ), namely: the sample powder 100cm 3 Slowly add until the capacity reaches 100cm 3 The measuring cylinder is plugged with a stopper and the measuring cylinder is dropped 250 times from a height of 5 cm. The mass (g) of the sample powder after 250 drops is divided by the volume (cm 3 ) is the value obtained.

[0098] The particle density of the carbon material is preferably less than or equal to 1.55 g / cm 3 , more preferably less than or equal to 1.50 g / cm 3 If the particle density is less than or equal to 1.55 g / cm 3 , there is a tendency to suppress the decrease in the ion concentration near the particles due to the spaces between the carbon material particles becoming too small when the electrode density is increased, thereby preventing the input and output characteristics of the lithium ion secondary battery from decreasing.

[0099] The particle density of the carbon material tends to decrease, for example, by reducing the volume average particle size of the carbon material. This property can be utilized to set the particle density within the above range.

[0100] The particle density of the entire negative electrode material including the carbon material may be 1.10 g / cm 3 ~2.00g / cm 3 As a method for adjusting the particle density of the negative electrode material, there is a method of controlling the temperature of the heat treatment performed on the carbon material.

[0101] In the present invention, the particle density of the carbon material or the negative electrode material refers to the value obtained as follows (g / cm 3 ), that is, 1.00 g of sample powder is put into the molding machine, and it is pressed with a pressure of 1.0 t by a hydraulic press, and the mass (g) is divided by the thickness (cm) and cross-sectional area (cm) of the sample after pressurization. 2 ) is the value obtained by the volume obtained.

[0102] The R value of the carbon material as measured by Raman spectroscopy is preferably 0.1 to 1.0, more preferably 0.2 to 0.8, and even more preferably 0.3 to 0.7. If the R value is 0.1 or greater, sufficient graphite lattice defects are present for lithium ion insertion and extraction, tending to suppress a decrease in input-output characteristics. If the R value is 1.0 or less, the decomposition reaction of the electrolyte is sufficiently suppressed, tending to suppress a decrease in primary efficiency.

[0103] The R value is defined as the wavelength at 1580 cm in the Raman spectrum obtained by Raman spectroscopy. -1 The intensity of the maximum peak near Ig and 1360 cm -1 Here, at 1580 cm -1 The peaks appearing near 1530 cm are usually identified as peaks corresponding to the graphite crystal structure, for example, -1 ~1630cm -1 In addition, at 1360cm -1Peaks appearing near 1300 cm are usually identified as peaks corresponding to the amorphous structure of carbon, for example, -1 ~1400cm -1 Observed peaks.

[0104] In this specification, Raman spectroscopy is measured using a laser Raman spectrophotometer (model: NRS-1000, JASCO Corporation) by irradiating a sample plate having a lithium ion secondary battery negative electrode material flattened thereon with argon laser light (excitation wavelength: 532 nm).

[0105] Examples of the carbon material include graphite (artificial graphite, natural graphite, graphitized mesophase carbon, graphitized carbon fiber, etc.), low-crystalline carbon, mesophase carbon, etc. From the perspective of increasing the charge and discharge capacity, it is preferred that at least a portion of the carbon material is graphite.

[0106] The shape of the carbon material is not particularly limited. For example, flaky, spherical, and massive shapes can be mentioned. From the perspective of obtaining a high tap density, a spherical shape is preferred. It is sufficient to appropriately select a carbon material having the above-mentioned physical properties from these carbon materials. One carbon material can be used alone, or two or more carbon materials having different materials, shapes, etc. can be used in combination.

[0107] The carbon material may also be a composite material comprising a first carbon phase serving as a core and a second carbon phase disposed on at least a portion of the surface thereof (e.g., coating the core) and different from the first carbon phase. By constituting the carbon material with a plurality of different carbon phases, a carbon material can be obtained that can more effectively exhibit desired physical properties or characteristics.

[0108] In the case where the carbon material is a composite material comprising a first carbon phase serving as a core and a second carbon phase disposed on at least a portion of the surface thereof, examples of the combination of the first carbon phase and the second carbon phase include a combination of the first carbon phase and the second carbon phase having a crystallinity different from that of the first carbon phase, preferably a combination of the first carbon phase and the second carbon phase having a crystallinity lower than that of the first carbon phase (d 002 is greater than the value of the first carbon phase.

[0109] When the carbon material is a composite material comprising a first carbon phase serving as a core and a second carbon phase having lower crystallinity than the first carbon phase, the material of the first carbon phase serving as the core is preferably selected from the above-mentioned graphite. In this case, the second carbon phase is preferably selected from a carbon phase having lower crystallinity than the first carbon phase (hereinafter also referred to as a low-crystalline carbon phase).

[0110] The material of the second carbon phase having lower crystallinity than the first carbon phase is not particularly limited and can be appropriately selected according to the desired properties. As a preferred example of the second carbon phase, a carbon phase obtained from an organic compound (carbon precursor) that can be converted into carbonaceous by heat treatment can be cited. Specifically, the following can be cited: ethylene heavy end fraction asphalt, crude oil asphalt, coal tar asphalt, asphalt decomposition asphalt, asphalt made by thermally decomposing organic compounds such as polyvinyl chloride, synthetic asphalt made by polymerizing naphthalene and the like in the presence of a superacid, etc. In addition, thermoplastic synthetic polymers such as polyvinyl chloride, polyvinyl alcohol, polyvinyl acetate, polyvinyl butyral; natural polymers such as starch and cellulose can also be used as carbon precursors.

[0111] When the carbon material is the composite material, the first carbon phase serving as the core preferably has an average interplanar spacing d of 1.5 to 2.5, from the viewpoint of increasing the charge-discharge capacity. 002 Graphite material with a range of 0.335nm to 0.339nm. 002 In the case of a graphite material having a diameter in the range of 0.335 nm to 0.338 nm, preferably in the range of 0.335 nm to 0.337 nm, the charge and discharge capacity is large, 330 mAh / g to 370 mAh / g, and there is a tendency that a good lithium ion secondary battery can be obtained.

[0112] The volume average particle size (50% D) of the graphite material that becomes the first carbon phase is preferably 1 μm to 20 μm. If the volume average particle size of the graphite material is greater than or equal to 1 μm, the raw graphite contains an appropriate amount of fine powder, which can suppress the aggregation in the process of making the organic compound as a carbon precursor adhere to the core material, and there is a tendency to mix the two more evenly. If the volume average particle size of the graphite material is less than or equal to 20 μm, there is a tendency to suppress the mixing of coarse particles in the negative electrode material, and to suppress the generation of streaks (muscles) when coating the negative electrode material.

[0113] The specific surface area of ​​the graphite material forming the first carbon phase, which is determined by nitrogen adsorption measurement at 77K, i.e., the BET specific surface area (N2 specific surface area), is preferably 0.1 m 2 / g~30m 2 / g, more preferably 0.5m 2 / g~25m 2 / g, more preferably 0.5m 2 / g~15m 2 / g. If the N2 specific surface area of ​​the graphite material is greater than or equal to 0.1m 2 / g, there is a tendency that agglomeration is difficult to occur in the process of attaching the organic compound as a carbon precursor to the core material. If the N2 specific surface area of ​​the graphite material is less than or equal to 30m 2 / g, the specific surface area can be maintained in an appropriate range, and the organic compound tends to adhere more uniformly.

[0114] Examples of the shape of the graphite material forming the first carbon phase include scaly, spherical, and massive shapes. From the viewpoint of increasing the tap density, a spherical shape is preferred.

[0115] An indicator of the sphericity of a graphite material is the aspect ratio. In this specification, the aspect ratio of a graphite material is a value obtained by dividing "maximum length perpendicular to maximum length" by "maximum length," with a maximum value of 1. Here, "maximum length" is the maximum distance between two points on the contour line of a graphite material particle, and "maximum length perpendicular to maximum length" is the length of the longest line segment connecting two points on the contour line of the particle, perpendicular to the line segment connecting the two points that will reach maximum length.

[0116] The aspect ratio of the graphite material can be measured using, for example, a flow-type particle image analyzer. Examples of the flow-type particle image analyzer include "FPIA-3000" manufactured by Sysmex Corporation.

[0117] The average aspect ratio of the graphite material becoming the first carbon phase is preferably greater than or equal to 0.1, more preferably greater than or equal to 0.3. If the average aspect ratio of the graphite material is greater than or equal to 0.1, the ratio of the flaky graphite in the graphite material will not be too much, and the amount of the edge face of the graphite material can be suppressed to within a suitable range. Because the edge face is active compared with the basal plane, there is the worry that the organic compound as a carbon precursor is attached to the edge face in the process of the core material, but if the average aspect ratio is greater than or equal to 0.1, there is the tendency that the organic compound is more uniformly attached to the core material. As a result, there is a tendency that the distribution of the low crystalline carbon and the crystalline carbon in the carbon material obtained becomes more uniform.

[0118] The negative electrode material may contain other components besides the carbon material as needed, such as a metal component.

[0119] As the metal component, for high capacity, as needed, the following can be listed: metal powder formed by elements alloyed with lithium, such as Al, Si, Ga, Ge, In, Sn, Sb, Ag, etc., multi-element alloy powders containing at least Al, Si, Ga, Ge, In, Sn, Sb, Ag, etc., and lithium alloy powders. The metal component can be used alone or in combination of two or more. In addition, when the negative electrode material includes a metal component, the metal component can be added separately from the carbon material, or it can be added in a state after being composited with the carbon material.

[0120] When the negative electrode material contains a metal component in addition to the carbon material, there is a tendency for the tap density of the negative electrode material as a whole to increase compared to the case where only the carbon material is contained. For example, the tap density of the negative electrode material as a whole can be made 0.3 g / cm 3 ~3.0g / cm 3 If the tap density of the negative electrode material is high, the charge and discharge reaction will be promoted, the negative electrode resistance will be reduced, and good input and output characteristics will tend to be obtained.

[0121] When the negative electrode material contains a metal component in addition to the carbon material, the amount thereof is not particularly limited and may be, for example, 1% to 50% by mass of the entire negative electrode material.

[0122] <Negative electrode materials for lithium-ion secondary batteries (2)>

[0123] The negative electrode material for lithium ion secondary batteries of this embodiment includes a carbon material, and the average interplanar spacing d of the carbon material obtained by X-ray diffraction is 002 The wavelength is 0.335 nm to 0.339 nm, the R value determined by Raman spectroscopy is 0.1 to 1.0, and the following (1) and (2) are satisfied.

[0124] (1) In the number-based particle size distribution, the particle diameter at which the differential relative particle amount q0 becomes the mode is 11.601 μm or less.

[0125] (2) In the number-based particle size distribution, the ratio (q0A / q0B) of the relative amount of differential particles q0A at a particle diameter of 11.601 μm to the relative amount of differential particles q0B at a particle diameter of 7.806 μm is 1.20 to 3.00.

[0126] For the details and preferred aspects of the conditions of the negative electrode material of this embodiment, reference can be made to the description related to the negative electrode material of the above embodiment.

[0127] <Negative electrode materials for lithium-ion secondary batteries (3)>

[0128] The negative electrode material for lithium ion secondary batteries of this embodiment includes a carbon material, and the average interplanar spacing d of the carbon material obtained by X-ray diffraction is 002 It is 0.335 nm to 0.339 nm, includes a first carbon phase as a core, and a second carbon phase different from the first carbon phase and arranged on at least a portion of the surface of the first carbon phase, and satisfies the following (1) and (2).

[0129] (1) In the number-based particle size distribution, the particle diameter at which the differential relative particle amount q0 becomes the mode is 11.601 μm or less.

[0130] (2) In the number-based particle size distribution, the ratio (q0A / q0B) of the relative amount of differential particles q0A at a particle diameter of 11.601 μm to the relative amount of differential particles q0B at a particle diameter of 7.806 μm is 1.20 to 3.00.

[0131] For the details and preferred aspects of the conditions of the negative electrode material of this embodiment, reference can be made to the description related to the negative electrode material of the above embodiment.

[0132] <Method for manufacturing negative electrode materials>

[0133] The method for producing the negative electrode material of the present embodiment is not particularly limited, and a method generally used in producing negative electrode materials can be employed.

[0134] When the carbon material is a composite material including a first carbon phase serving as a core and a second carbon phase disposed on at least a portion of the surface thereof, a method for producing the composite material may include, for example, a method in which an organic compound serving as a carbon precursor is attached to the surface of the core material serving as the first carbon phase, and then the carbon precursor is carbonized by firing in an inert atmosphere at 750° C. to 1200° C. The organic compound used as the carbon precursor may be the organic compounds described above as examples of the carbon precursor.

[0135] There are no particular limitations on the method for attaching the carbon precursor to the surface of the first carbon phase. Examples include a wet method in which a liquid obtained by dissolving or dispersing the carbon precursor in a solvent is mixed with the core material to form the first carbon phase, and then the solvent is removed; a dry method in which the core material and the carbon precursor are mixed in solid form to obtain a mixture, and mechanical energy is applied to the mixture to cause the mixture to adhere; and a gas phase method such as CVD. From the perspective of controlling the specific surface area of ​​the carbon material, a dry method is preferred.

[0136] There is no particular limitation on the method for attaching a carbon precursor to the surface of the first carbon phase by a dry method. For example, a mixture of the first carbon and the carbon precursor can be filled into a container having a structure capable of mixing and stirring at least one of the contents, and mechanical energy is applied and at least one of mixing and stirring is performed, thereby attaching. Specifically, for example, a container having a device such as a blade or a screw can be used. There is no particular limitation on the amount of mechanical energy applied to the mixture. For example, it is preferably 0.360kJ / kg to 36000kJ / kg, more preferably 0.360kJ / kg to 7200kJ / kg, and further preferably 2.50kJ / kg to 2000kJ / kg.

[0137] Here, the mechanical energy applied to the mixture is a value obtained by multiplying the time (h) by the load (kW) and dividing it by the mass (kg) of the filled mixture. By setting the mechanical energy applied to the mixture to the above range, the carbon precursor is more evenly attached to the surface of the first carbon, and the distribution of low-crystalline carbon and crystalline carbon in the obtained carbon material tends to become more uniform.

[0138] The substance (intermediate product) in the state after the carbon precursor is attached to the surface of the first carbon phase is further heated and fired. The firing temperature is not particularly limited as long as it is a temperature at which the carbon precursor can be carbonized. For example, it is preferably 750°C to 2000°C, more preferably 800°C to 1800°C, and even more preferably 900°C to 1400°C. If the firing temperature is greater than or equal to 750°C, there is a tendency to be able to well maintain the charge and discharge efficiency, input and output characteristics and cycle characteristics of the lithium ion secondary battery. If the firing temperature is less than or equal to 2000°C, there is a tendency to be able to suppress the crystallinity of the low crystalline carbon part from becoming too high. As a result, there is a tendency to be able to well maintain characteristics such as fast charging characteristics, low temperature charging characteristics, and overcharge safety. The atmosphere during firing is not particularly limited as long as it is an atmosphere that is difficult for the intermediate product to oxidize. For example, a nitrogen atmosphere, an argon atmosphere, a self-decomposition gas atmosphere, etc. can be applied. The form of the furnace used for firing is not particularly limited. For example, an intermittent furnace, a continuous furnace, etc. that uses at least one of electricity and gas as a heat source are preferred.

[0139] <Negative electrodes for lithium-ion secondary batteries>

[0140] The negative electrode for a lithium-ion secondary battery of this embodiment comprises: a negative electrode material layer comprising the aforementioned negative electrode material, and a current collector. This allows for a lithium-ion secondary battery to be constructed that maintains high charge and discharge efficiency while also exhibiting excellent input / output characteristics and lifespan characteristics. In addition to the negative electrode material layer comprising the aforementioned negative electrode material and the current collector, the negative electrode for a lithium-ion secondary battery may also contain other components as needed.

[0141] There are no particular restrictions on the method for producing a negative electrode for a lithium-ion secondary battery. For example, the following methods may be used: a method in which the negative electrode material, an organic binder, and a solvent are kneaded together using a dispersing device such as a blender, a ball mill, a super sand mill, or a pressure kneader to prepare a slurry of the negative electrode composition, which is then applied to the surface of the current collector to form a negative electrode layer; a method in which a paste of the negative electrode composition is prepared in the same manner as above, and the paste is formed into a sheet, granules, or other form, which is then integrated with the current collector.

[0142] The organic binder is not particularly limited. Examples include styrene-butadiene copolymers, methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, (meth)acrylonitrile, and hydroxyethyl (meth)acrylate; ethylenically unsaturated carboxylic acids such as acrylic acid, methacrylic acid, itaconic acid, fumaric acid, and maleic acid; and polymers with high ion conductivity such as polyvinylidene fluoride, polyethylene oxide, polyepichlorohydrin, polyphosphazene, and polyacrylonitrile. (Meth)acrylate refers to at least one of acrylate and methacrylate.

[0143] The amount of the organic binder contained in the negative electrode composition is not particularly limited, but is preferably 0.5 to 20 parts by mass based on 100 parts by mass of the total of the negative electrode material and the organic binder.

[0144] The negative electrode composition may contain a thickener for adjusting the viscosity. Examples of the thickener include carboxymethyl cellulose, methyl cellulose, hydroxymethyl cellulose, ethyl cellulose, polyvinyl alcohol, polyacrylic acid (salt), oxidized starch, phosphorylated starch, and casein.

[0145] The negative electrode composition may also contain a conductive auxiliary material. Examples of conductive auxiliary materials include carbon materials such as carbon black, graphite, and acetylene black, as well as conductive oxides and nitrides. The amount of conductive auxiliary material is not particularly limited, but may be approximately 0.5% to 15% by mass relative to 100 parts by mass of the negative electrode material.

[0146] The material and shape of the current collector are not particularly limited. For example, a current collector obtained by forming a metal material such as aluminum, copper, nickel, titanium, stainless steel into a foil, an open-hole foil, a mesh, etc. can be cited. Furthermore, porous materials such as porous metal (foamed metal), carbon paper, etc. can also be used.

[0147] The method for applying the negative electrode composition to the current collector is not particularly limited. For example, coating methods such as metal mask printing, electrostatic coating, dip coating, spraying, roller coating, doctor blade coating, notch wheel coating, gravure coating, and screen printing can be mentioned. After the negative electrode composition is applied to the current collector, in order to remove the solvent contained in the negative electrode composition, it is dried using a hot air dryer, an infrared dryer, or a dryer combined therewith. Furthermore, a flat press, a calendering roller, etc. may be used for calendering as needed.

[0148] The method for forming the negative electrode material composition into a sheet, pellet, or other form and integrating it with the current collector is not particularly limited. For example, this can be done using a roller, a press, or a combination thereof using known methods. The pressure during integration is preferably between 1 mPa and 200 mPa.

[0149] The negative electrode density of the negative electrode for lithium ion secondary batteries is preferably 1.3 g / cm 3 ~1.8g / cm 3 , more preferably 1.4 g / cm 3 ~1.8g / cm 3 , more preferably 1.5 g / cm 3 ~1.7g / cm 3 If the negative electrode density is greater than or equal to 1.3g / cm 3 , there is a tendency that the resistance value is not easy to decrease and the capacity can be maintained high. If it is less than or equal to 1.8g / cm 3 , there is a tendency to suppress the decline in rate characteristics and cycle characteristics.

[0150] <Lithium-ion secondary batteries>

[0151] The lithium-ion secondary battery of this embodiment includes the above-mentioned negative electrode for lithium-ion secondary battery, a positive electrode, and an electrolyte. The lithium-ion secondary battery can be obtained, for example, by arranging the negative electrode and the positive electrode for lithium-ion secondary battery in a container so as to face each other with a separator interposed therebetween, and injecting an electrolyte solution prepared by dissolving the electrolyte in a solvent into the container.

[0152] The positive electrode can be obtained by applying a positive electrode material to the surface of a current collector to form a positive electrode layer, similar to the negative electrode. As the current collector, a strip-shaped current collector formed of a metal material such as aluminum, titanium, or stainless steel into a foil, perforated foil, or mesh can be used.

[0153] The material used for the positive electrode is not particularly limited, and examples thereof include positive electrode active materials such as metal compounds, metal oxides, metal sulfides, and phosphoric acid compounds that can be doped or inserted with lithium ions, and other materials.

[0154] Examples of positive electrode active materials include lithium cobaltate (LiCoO2), lithium nickelate (LiNiO2), lithium manganate (LiMnO2), and composite oxides in which at least a portion of the cobalt in lithium cobaltate is replaced by at least one of nickel and manganese (LiCo x Ni y Mn z O2, x+y+z=1), a composite oxide in which at least a portion of cobalt, nickel and manganese in these compounds is replaced by an additional element M' (LiCo a Ni b Mn c M' d O2, a+b+c+d=1, M': Al, Mg, Ti, Zr or Ge), lithium manganese spinel (LiMn2O4), lithium vanadium compounds, V2O5, V6O 13, VO2, MnO2, TiO2, MoV2O8, TiS2, V2S5, VS2, MoS2, MoS3, Cr3O8, Cr2O5, and olivine-type LiMPO4 (M: Co, Ni, Mn, Fe).

[0155] Examples of other materials include conductive polymers such as polyacetylene, polyaniline, polypyrrole, polythiophene, and polyacene, and porous carbon.

[0156] Examples of the separator include nonwoven fabrics, cloths, microporous films, and combinations thereof, primarily made of polyolefins such as polyethylene and polypropylene. It should be noted that in lithium-ion secondary batteries where the positive electrode and negative electrode are not in contact, the separator may be omitted.

[0157] Examples of the electrolyte include lithium salts such as LiClO 4 , LiPF 6 , LiAsF 6 , LiBF 4 , and LiSO 3 CF 3 .

[0158] Examples of the solvent for dissolving the electrolyte include non-aqueous solvents such as ethylene carbonate, fluoroethylene carbonate, chloroethylene carbonate, propylene carbonate, butylene carbonate, vinylene carbonate, cyclopentanone, cyclohexylbenzene, sulfolane, propane sultone, 3-methylsulfolane, 2,4-dimethylsulfolane, 3-methyl-1,3-oxazolidin-2-one, γ-butyrolactone, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methylpropyl carbonate, butylmethyl carbonate, ethylpropyl carbonate, butylethyl carbonate, dipropyl carbonate, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, methyl acetate, ethyl acetate, trimethyl phosphate, and triethyl phosphate.

[0159] The configuration of the electrodes in a lithium-ion secondary battery is not particularly limited. Generally, examples include a configuration in which the positive electrode and the negative electrode, and a separator provided between the positive electrode and the negative electrode as needed, are stacked and then wound into a spiral shape (a wound electrode plate assembly) and a plate-like configuration that is not wound into a spiral shape (a stacked electrode plate assembly).

[0160] The type of lithium ion secondary battery is not particularly limited, and examples thereof include laminated batteries, paper batteries, button batteries, coin batteries, stacked batteries, cylindrical batteries, and square batteries.

[0161] The negative electrode material of this embodiment has excellent input / output characteristics and lifespan during charge and discharge, and is therefore suitable for use in lithium-ion secondary batteries requiring larger capacities, such as electric vehicles, power tools, and power storage applications. In particular, in automotive applications such as electric vehicles (EVs), hybrid electric vehicles (HEVs), and plug-in hybrid electric vehicles (PHEVs), high current charge and discharge are required to improve acceleration and regenerative braking performance. It is desirable to use the negative electrode material of this embodiment, which not only meets these requirements but also has excellent input / output characteristics.

[0162] Example

[0163] Hereinafter, the present invention will be further specifically described with reference to Examples, but the present invention is not limited to the following Examples.

[0164] [Example 1]

[0165] The spherical natural graphite (d 002 =0.336nm, average aspect ratio = 0.8) 100 parts by mass of spherical natural graphite (softening point 98 ° C, residual carbon rate (carbonization rate) 50%) and 5 parts by mass of coal tar pitch (softening point 98 ° C, residual carbon rate (carbonization rate) 50%) are placed in a barrel equipped with rotating blades, and the inner wall of the barrel and the rotating blades are rubbed against each other, so that the coal tar pitch adheres to the surface of the spherical natural graphite. The mutual friction process is carried out for 5 minutes under a load of 24kW (load: 1800kJ / kg). Then, under nitrogen flow, the temperature is raised to 1000 ° C at a heating rate of 20 ° C / hour and maintained for 1 hour to carbonize the coal tar pitch. Then, it is crushed using a cutting grinder and sieved using a 300-mesh sieve to obtain the undersize portion as composite material 1.

[0166] Spherical natural graphite with a volume average particle size of 16 μm (d 002 Composite material 2 was obtained in the same manner as composite material 1 except that 100 parts by mass of spherical natural graphite having a volume average particle size of 10 μm was used instead of composite material 1 (=0.336 nm, average aspect ratio=0.8).

[0167] Composite material 1 and composite material 2 were mixed in a mass ratio of 5:5 (composite material 1: composite material 2) to prepare a carbon material. The obtained carbon material was subjected to XRD analysis, specific surface area measurement, particle size distribution measurement, tap density measurement, and particle density measurement by the methods shown below.

[0168] [XRD analysis (average interplanar spacing d 002 Determination of

[0169] The carbon material was filled into the concave portion of a quartz sample holder, which was then placed on a measuring table, and measured using a wide-angle X-ray diffractometer (manufactured by Rigaku Corporation) under the following measurement conditions.

[0170] Radiation source: CuKα ray (wavelength = 0.15418nm)

[0171] Output: 40kV, 20mA

[0172] Sampling amplitude: 0.010°

[0173] Scanning range: 10°~35°

[0174] Scanning speed: 0.5° / min

[0175] [N2 specific surface area measurement]

[0176] For carbon materials, nitrogen adsorption at liquid nitrogen temperature (77K) was measured by a multipoint method using a high-speed specific surface area / pore distribution measuring apparatus ("ASAP2010" from MICROMERITICS), and the adsorption was calculated by the BET method (relative pressure range: 0.05 to 0.2).

[0177] [Particle size distribution measurement]

[0178] A solution prepared by dispersing the carbon material and a surfactant in purified water was placed in the sample water tank of a laser diffraction particle size distribution analyzer ("SALD-3000J" manufactured by Shimadzu Corporation). The solution was circulated by a pump while ultrasonic waves were applied for 1 minute. The laser diffraction method was used for measurement under the following measurement conditions. The output conditions were set to the number or volume basis, and the values ​​that met the following (1) to (5) were examined.

[0179] (Setting of measurement conditions)

[0180] Number of measurements: 1

[0181] Measurement interval: 2 seconds

[0182] Average number of times: 64 times

[0183] Absorbance range: 0.01~0.2

[0184] (Any particle size % table setting)

[0185] Range: 0.1μm~2000μm

[0186] Number of divisions: 50

[0187] (1) In the particle size distribution measurement described above, the particle size at which the differential relative particle amount q0 becomes the mode in the number-based particle size distribution obtained by setting the distribution basis of the output condition to "number" is examined.

[0188] (2) Calculate the ratio (q0A / q0B) of the relative particle amount q0A of the difference when the particle size is 11.601 μm to the relative particle amount q0B of the difference when the particle size is 7.806 μm in the number-based particle size distribution obtained by setting the distribution basis of the output condition to "number" in the above-mentioned particle size distribution measurement.

[0189] (3) In the volume-based particle size distribution obtained by setting the distribution basis of the output conditions to "volume" in the above-mentioned particle size distribution measurement, when the volume cumulative distribution curve is drawn from the smaller particle size side, the cumulative value Q3 at a particle size of 9.516 μm is examined.

[0190] (4) In the volume-based particle size distribution obtained by setting the distribution basis of the output conditions to "volume" in the above-mentioned particle size distribution measurement, the particle size (50% D) at which the accumulation reaches 50% when the volume cumulative distribution curve is drawn from the smaller particle size side is examined.

[0191] (5) In the volume-based particle size distribution obtained by setting the distribution basis of the output conditions to "volume" in the above-mentioned particle size distribution measurement, the particle size (99.9% D) at which the cumulative volume reaches 99.9% when the volume cumulative distribution curve is drawn from the smaller particle size side is examined.

[0192] [Tap density measurement]

[0193] The carbon material 100cm 3 Slowly add until the capacity reaches 100cm 3 The measuring cylinder was plugged and the measuring cylinder was dropped 250 times from a height of 5 cm. The mass and volume of the carbon material after the 250 drops were determined as the tap density.

[0194] [Particle density measurement]

[0195] 1.00 g of carbon material was placed in a 13 mm diameter molding die (Carver's 13 mm pellet die model 3619), and pressurized at a pressure of 1.0 t using a hydraulic press (Carver's "Carver Standard Press"). The volume calculated based on the thickness and cross-sectional area of ​​the pressurized carbon material was divided by the mass of the carbon material to obtain the particle density.

[0196] [Average aspect ratio]

[0197] The average aspect ratio of the carbon material was determined using a flow particle image analyzer ("FPIA-3000" manufactured by Sysmex Corporation).

[0198] [Determination of initial charge and discharge efficiency]

[0199] To 98 parts by mass of the carbon material produced, an aqueous solution of CMC (carboxymethyl cellulose, "Cellogen WS-C" from Daiichi Kogyo Seiyaku Co., Ltd.) as a thickener was added in an amount of 1 part by mass of the solid content of CMC, and the CMC concentration of the aqueous solution was 2% by mass, and kneading was performed for 10 minutes. Next, purified water was added in an amount of 40% to 50% by mass of the solid content concentration in the kneaded product (the total of the negative electrode material and CMC), and kneading was performed for 10 minutes. Next, an aqueous dispersion of SBR ("BM-400B" from ZEON Co., Ltd. of Japan) as a binder was added in an amount of 1 part by mass of the solid content of SBR, and the SBR concentration of the aqueous dispersion was 40% by mass, and mixed for 10 minutes to produce a paste-like negative electrode material composition. The negative electrode material composition was applied to an electrolytic copper foil with a thickness of 40 μm in a circular shape with a diameter of 9.5 mm using a mask with a thickness of 200 μm. Furthermore, the resulting mixture was dried at 105° C. to remove moisture, thereby producing a sample electrode (negative electrode).

[0200] Next, the sample electrode, separator, and counter electrode were stacked in this order and placed in a battery container. A coin cell was prepared by injecting an electrolyte solution consisting of LiPF₆ dissolved at a concentration of 1.5 mol / L in a mixed solvent of ethylene carbonate (EC) and methyl ethyl carbonate (MEC) (EC:MEC volume ratio of 1:3). Metallic lithium was used for the counter electrode, and a 20 μm-thick polyethylene microporous membrane was used for the separator.

[0201] The obtained coin cell was charged between the sample electrode and the counter electrode at 0.2 mA / cm 2 The constant current is charged to 0V (Vvs.Li / Li + ), then, the battery was charged at a constant voltage of 0 V until the current reached 0.02 mA. Then, after a rest period of 30 minutes, the battery was charged at a constant voltage of 0.2 mA / cm 2 The constant current discharge is 2.5V (Vvs.Li / Li + ) and measure the initial charge-discharge efficiency. The initial charge-discharge efficiency (%) is calculated as (discharge capacity) / (charge capacity) × 100. Here, charging refers to the case where the negative electrode material sample electrode absorbs lithium ions, while discharging refers to the case where the sample electrode releases lithium ions.

[0202] [Evaluation of life characteristics]

[0203] The coating amount per unit area was 9.0 mg / cm 2 The negative electrode material composition prepared in the same manner as the negative electrode material composition used to measure the initial charge and discharge efficiency was applied to a 40 μm thick electrolytic copper foil using a notched wheel coater with the gap adjusted in a manner. The electrode density was then adjusted to 1.5 g / cm using a manual press. 3 This electrode was punched into a disk shape with a diameter of 14 mm to prepare a sample electrode (negative electrode). Using this sample electrode, a coin battery was prepared in the same manner as in the measurement of the initial charge and discharge efficiency except for the above.

[0204] Using the coin cells produced above, life characteristics were evaluated according to the following procedures.

[0205] (1) Charge to 0V (Vvs.Li / Li) at a constant current of 0.48mA + ), then charge at a constant voltage of 0 V until the current reaches 0.048 mA.

[0206] (2) After a rest period of 30 minutes, the battery was discharged at a constant current of 0.48 mA to a voltage of 1.5 V (V vs. Li / Li) + ) and measured the discharge capacity.

[0207] (3) Charge to 0V (Vvs.Li / Li) at a constant current of 4.8mA + ), charge at a constant voltage of 0V until the current reaches 0.48mA.

[0208] (4) After a rest period of 30 minutes, discharge the battery at a constant current of 4.8 mA to 1.5 V (V vs. Li / Li + )until.

[0209] (5) The charge-discharge cycle test of (3) and (4) above was carried out for 50 cycles.

[0210] When the above cycle was repeated 50 times, the discharge capacity retention rate from the first cycle was measured (= discharge capacity at the 50th cycle / discharge capacity at the first cycle × 100). The higher the discharge capacity retention rate, the better the lifespan characteristics.

[0211] (Evaluation of input and output characteristics)

[0212] Coin batteries were produced by the same method as for the life characteristics, and their input-output characteristics were evaluated according to the following procedures.

[0213] (1) Charge to 0V (Vvs.Li / Li) at a constant current of 0.96mA +), and then, constant voltage charging was performed at 0 V until the current value reached 0.096 mA.

[0214] (2) After a rest period of 30 minutes, discharge the battery at a constant current of 0.96 mA to 1.5 V (V vs. Li / Li + )until.

[0215] (3) Charge at a constant current of 0.96 mA until the battery reaches half of its capacity.

[0216] (4) Discharge for 10 seconds at currents of 4.8 mA, 14.4 mA, and 24 mA, and check the voltage drop (ΔV) at that time. A rest period of 30 minutes was set between the tests at each current value.

[0217] ΔV is plotted against each current value, and its slope is defined as the resistance value (Ω). The smaller this value, the better the input-output characteristics.

[0218] [Example 2]

[0219] A carbon material was prepared in the same manner as in Example 1, except that Composite Material 1 and Composite Material 2 were mixed at a mass ratio of 4:6 (Composite Material 1:Composite Material 2). Its properties were investigated. In addition, coin cells were prepared and their performance evaluated. The results are shown in Table 2.

[0220] [Example 3]

[0221] A carbon material was prepared in the same manner as in Example 1, except that Composite Material 1 and Composite Material 2 were mixed at a mass ratio of 3:7 (Composite Material 1:Composite Material 2). Its properties were investigated. In addition, coin cells were prepared and their performance evaluated. The results are shown in Table 2.

[0222] [Example 4]

[0223] A carbon material was prepared in the same manner as in Example 1, except that Composite Material 1 and Composite Material 2 were mixed at a mass ratio of 6:4 (Composite Material 1:Composite Material 2). Its properties were investigated. In addition, coin cells were prepared and their performance evaluated. The results are shown in Table 2.

[0224] [Comparative Example 1]

[0225] A carbon material was prepared in the same manner as in Example 1, except that Composite Material 1 and Composite Material 2 were mixed at a mass ratio of 2:8 (Composite Material 1:Composite Material 2). Its properties were investigated. In addition, coin cells were prepared and their performance evaluated. The results are shown in Table 2.

[0226] [Comparative Example 2]

[0227] A carbon material was prepared in the same manner as in Example 1 except that only Composite Material 2 was used, and its properties were examined. In addition, a coin cell was prepared and its performance was evaluated. The results are shown in Table 2.

[0228] [Comparative Example 3]

[0229] A carbon material was produced in the same manner as in Example 1, except that only Composite Material 1 was used, and its properties were examined. In addition, a coin cell was produced and its performance was evaluated. The results are shown in Table 2.

[0230] [Comparative Example 4]

[0231] Spherical natural graphite with a volume average particle size of 22 μm (d 002 Composite material 3 was obtained in the same manner as composite material 1 except that 100 parts by mass of spherical natural graphite having a volume average particle size of 10 μm was used instead of composite material 1 (average particle size = 0.336 nm, average aspect ratio = 0.7).

[0232] A carbon material was prepared in the same manner as in Example 1, except that Composite Material 3 and Composite Material 2 were mixed at a mass ratio of 5:5 (Composite Material 3:Composite Material 2). Its properties were investigated. In addition, coin cells were prepared and their performance evaluated. The results are shown in Table 2.

[0233] [Comparative Example 5]

[0234] Spherical natural graphite with a volume average particle size of 22 μm (d 002 =0.336nm, average aspect ratio = 0.7) was passed through a 300-mesh sieve, and the resulting undersize fraction was mixed with Composite Material 2 at a mass ratio of 5:5 (undersize fraction: Composite Material 2). A carbon material was produced and its properties were investigated in the same manner as in Example 1. Coin batteries were also produced and their performance evaluated. The results are shown in Table 2.

[0235] [Comparative Example 6]

[0236] Coal-based coal tar was heat-treated at 400°C in an autoclave to obtain crude coke. The crude coke was crushed and then calcined in an inert atmosphere at 1200°C to obtain coke blocks. The coke blocks were crushed into an average particle size of 15 μm using an impact crusher equipped with a classifier, and then passed through a 200-mesh sieve to obtain the undersize fraction as carbon particles (d 002 =0.342 nm). Composite material 4 was obtained in the same manner as composite material 1 except that 100 parts by mass of the carbon particles were mixed with 20 parts by mass of polyvinyl alcohol (polymerization degree 1700, completely saponified type, carbonization rate 15% by mass).

[0237] A carbon material was prepared in the same manner as in Example 1, except that Composite Material 4 and Composite Material 2 were mixed at a mass ratio of 5:5 (Composite Material 4:Composite Material 2). Its properties were investigated. In addition, coin cells were prepared and their performance evaluated. The results are shown in Table 2.

[0238] [Comparative Example 7]

[0239] Spherical natural graphite with a volume average particle size of 10 μm (d 002 = 0.336nm, average aspect ratio = 0.8) and spherical natural graphite with a volume average particle size of 16μm (d 002 =0.336 nm, average aspect ratio = 0.8) were mixed at a mass ratio of 5:5. A carbon material was prepared in the same manner as in Example 1, and its properties were investigated. In addition, coin cells were prepared and their performance evaluated. The results are shown in Table 2.

[0240] [Comparative Example 8]

[0241] The carbon particles (d 002 =0.342nm) 100 parts by mass of coal tar pitch, 30 parts by mass of iron oxide powder and 5 parts by mass of iron oxide powder were mixed at 250°C for 1 hour. The obtained block was crushed by a pin mill and then formed into a density of 1.52 g / cm by a molding press. 3 in the form of a block. The obtained block was sintered at a maximum temperature of 800°C in a muffle furnace and then graphitized at 2900°C in an Acheson furnace under a self-decomposition gas atmosphere. Next, the graphitized block was coarsely crushed with a hammer and a graphite powder with an average particle size of 30 μm was obtained by a pin mill. Furthermore, the graphite powder was treated for 10 minutes using a spheroidizing treatment device (manufactured by Hosokawa Micron, Faculty) at a crushing speed of 1800 rpm and a classification speed of 7000 rpm to produce spheroidized artificial graphite powder. The spheroidized artificial graphite powder was passed through a 200-mesh sieve, and the undersize portion was obtained as a carbon material. The same operation as in Example 1 was performed to investigate the properties of the carbon material. In addition, coin batteries were produced and their performance was evaluated. The results are shown in Table 2.

[0242] [Table 2]

[0243]

[0244] The results shown in Table 2 show that the lithium ion secondary batteries of Examples 1 to 4 produced using the negative electrode material containing the carbon material of this embodiment maintain high charge and discharge efficiency while also having excellent input and output characteristics and life characteristics.

Claims

1. A negative electrode material for a lithium ion secondary battery, comprising a carbon material, The average interplanar spacing d of the carbon material obtained by X-ray diffraction 002 The specific surface area is 0.335nm to 0.339nm, and the specific surface area is 0.5m 2 / g~6.0m 2 / g, The carbon material is a composite material including a first carbon phase serving as a core and a second carbon phase disposed at least partially on the surface thereof, and the R value measured by Raman spectroscopy is 0.1 to 1.

0. The carbon material satisfies the following (1) and (2), (1) In the particle size distribution based on the number of particles, the particle size at which the differential relative particle amount q0 becomes the most frequent value is less than or equal to 11.601 μm, (2) In the particle size distribution based on number, the ratio of the relative difference amount q0A when the particle diameter is 11.601 μm to the relative difference amount q0B when the particle diameter is 7.806 μm, that is, q0A / q0B is 1.20 to 3.

00.

2. The negative electrode material for a lithium ion secondary battery according to claim 1, wherein in the volume-based particle size distribution of the carbon material, when a volume cumulative distribution curve is drawn from the smaller particle size side, the cumulative value Q3 when the particle size is 9.516 μm is greater than or equal to 4.0% of the total.

3. The negative electrode material for lithium ion secondary battery according to claim 1 or 2, wherein in the volume-based particle size distribution of the carbon material, when a volume cumulative distribution curve is drawn from the smaller particle size side, the particle size at which the cumulative amount reaches 50%, i.e., 50%D, is 1 μm to 20 μm.

4. A negative electrode material for a lithium ion secondary battery according to claim 1 or 2, wherein in the volume-based particle size distribution of the carbon material, when a volume cumulative distribution curve is drawn from the small particle size side, the particle size at which the accumulation becomes 99.9%, i.e., 99.9%D, is less than or equal to 63 μm.

5. The negative electrode material for lithium ion secondary battery according to claim 1 or 2, wherein the tap density of the carbon material is 0.90 g / cm 3 ~2.00g / cm 3 .

6. The negative electrode material for lithium ion secondary battery according to claim 1 or 2, wherein the particle density of the carbon material is less than or equal to 1.55 g / cm 3 . 7 . A negative electrode for a lithium ion secondary battery, comprising a negative electrode material layer and a current collector, wherein the negative electrode material layer comprises the negative electrode material for a lithium ion secondary battery according to claim 1 . 8 . A lithium ion secondary battery comprising the negative electrode for a lithium ion secondary battery according to claim 7 , a positive electrode, and an electrolyte.

Citation Information

Patent Citations

  • Electrode for secondary battery

    JP1992370662A

  • Nonaqueous group secondary battery

    JP1993307956A

  • Nonaqueous electrolyte secondary battery

    JP2015082381A

  • Carbon material for nonaqueous secondary battery and nonaqueous secondary battery

    JP2015185443A

  • Novel graphite grobule and carbonaceous material usingsame

    KR1020050106537A